Enhancing Speaking Proficiency Through Integrated Language Assessment In Efl Classrooms: A Case Study At SMAN 2 Unggulan Talang Ubi - Rimadhona, Marizka; Firdaus, Masagus (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking is a critical language skill in EFL learning, yet it remains one of the most challenging to assess effectively. This study investigates the integration of language assessment with speaking skills at SMAN 2 Unggulan Talang Ubi. Through a qualitative descriptive approach, the study explores how teachers implement speaking assessments, how these assessments align with instructional objectives, and their perceived impact on students’ speaking performance. Data were collected via classroom observations, teacher interviews, and student focus group discussions. The findings indicate that performance-based assessments, particularly role plays and oral presentations, enhance students’ speaking proficiency, motivation, and confidence. The study concludes with pedagogical implications for aligning assessment with communicative teaching goals and recommends more structured feedback mechanisms to support learners’ oral language development.